2004
DOI: 10.1016/j.jacc.2004.09.020
|View full text |Cite
|
Sign up to set email alerts
|

Accurate and objective infarct sizing by contrast-enhanced magnetic resonance imaging in a canine myocardial infarction model

Abstract: When an objective technique is used to define MI size by CE-MRI, accurate infarct size measurements can be obtained from images obtained up to 30 min after contrast administration.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

8
395
1
1

Year Published

2006
2006
2017
2017

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 455 publications
(405 citation statements)
references
References 22 publications
8
395
1
1
Order By: Relevance
“…The extent of LGE as a percentage of LV mass was calculated automatically by the software. The full width at half maximum method17 was used for defining the threshold for LGE: Tissue with a signal intensity >50% of the maximum signal of the enhanced myocardium was quantified as scar tissue. In T2‐weighted images, regions of interest were drawn on remote skeletal muscle and on the LV segments in which myocardial edema was suspected.…”
Section: Methodsmentioning
confidence: 99%
“…The extent of LGE as a percentage of LV mass was calculated automatically by the software. The full width at half maximum method17 was used for defining the threshold for LGE: Tissue with a signal intensity >50% of the maximum signal of the enhanced myocardium was quantified as scar tissue. In T2‐weighted images, regions of interest were drawn on remote skeletal muscle and on the LV segments in which myocardial edema was suspected.…”
Section: Methodsmentioning
confidence: 99%
“…The gray scale LGE MRI images (2D slices), with voxel size of 1 mm 3 , were analyzed and five different tissue types were defined based on the pattern of enhancement 14. The enhancement was categorized by the number of standard deviations (SD) above the mean intensity of a remote area of normal tissue on each slice (baseline intensity).…”
Section: Methodsmentioning
confidence: 99%
“…This is because it has been conclusively shown that delayed hyper-enhancement seen on MRI (DE-MRI) is exclusively associated with myocyte necrosis. 8,9 The utility of CMRI in apical ballooning was recently investigated by Mitchell et al 10 Though, there were concerns about resolution of CMRI to detect changes at microscopic level, excellent correlation has been shown between DE-MRI and histopathology even for small infarcts. 8,9,11,12 It is important to note that regions subjected to severe but reversible ischaemic injuries do not hyper-enhance on DE-MRI, even in the presence of myocardial stunning.…”
Section: Discussionmentioning
confidence: 99%